The Effect of Cognitive Behavioral Therapy (CBT) on Reducing Anxiety Levels in Patients with Bipolar Affective Disorder at the Mental Health Clinic of Dr. MM Dunda Limboto Regional General Hospital - Sopyan Ntau; Fifi Ishak; Nur Uyuun I. Biahimo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
People with bipolar disorder experience anxiety disorders in 90% of cases. Anxiety disorders are comorbid disorders and can exacerbate the condition of people with bipolar disorder. Anxiety arises because of stimuli that are interpreted as danger or threats by people with bipolar disorder. The purpose of this study is to determine the effect of cognitive behavioral therapy (CBT) on reducing anxiety levels in patients with bipolar affective disorder at the Mental Health Clinic of Dr. MM Dunda Limboto General Hospital. The study design is a pre-experimental design with a one-group pretest-posttest design. The population consists of all patients with bipolar affective disorder, and the sample size, determined using purposive sampling, is 30 respondents. The data were analyzed using a paired t-test. The results of the study showed that the significance value (p-value) was 0.000 (p < 0.05), indicating that there is an effect of cognitive behavioral therapy (CBT) on reducing anxiety levels in patients with bipolar affective disorder at the Psychiatric Clinic of Dr. MM Dunda Limboto General Hospital. The results of the study are expected to be applied in reducing anxiety levels in patients with bipolar disorder.